2015
DOI: 10.1002/dmrr.2672
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean diet and 10‐year incidence (2002–2012) of diabetes: correlations with inflammatory and oxidative stress biomarkers in the ATTICA cohort study

Abstract: The reported results support the role of Mediterranean diet as a promising dietary tool for the primary prevention of diabetes, by attenuating inflammation and fostering total antioxidant capacity. This dietary pattern may have therapeutic potential for many cardiometabolic disorders associated with inflammation and/or oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 38 publications
5
85
0
Order By: Relevance
“…A recent analysis of the 10-year results of the ATTICA cohort study revealed that the risk of diabetes decreased by 49% and 62%, respectively, with medium and high adherence to the Mediterranean diet in the general nondiabetic population [6]. The present results show that the protective effect of the Mediterranean diet is even stronger in subjects with prediabetes, suggesting that this dietary pattern is protective over the entire spectrum of non-diabetic subjects including subjects with prediabetes.…”
Section: Level Of Adherence To the Mediterranean Dietsupporting
confidence: 57%
See 2 more Smart Citations
“…A recent analysis of the 10-year results of the ATTICA cohort study revealed that the risk of diabetes decreased by 49% and 62%, respectively, with medium and high adherence to the Mediterranean diet in the general nondiabetic population [6]. The present results show that the protective effect of the Mediterranean diet is even stronger in subjects with prediabetes, suggesting that this dietary pattern is protective over the entire spectrum of non-diabetic subjects including subjects with prediabetes.…”
Section: Level Of Adherence To the Mediterranean Dietsupporting
confidence: 57%
“…The antidiabetic effect of the Mediterranean diet in the non-diabetic population of the ATTICA cohort was mediated by attenuation of inflammation and enhancement of total antioxidant capacity [6].…”
Section: Level Of Adherence To the Mediterranean Dietmentioning
confidence: 92%
See 1 more Smart Citation
“…400 BC), the concept of "food as medicine and medicine as food" has been followed and practiced among the different Western cultures. In the last few decades, several studies have shown that the Mediterranean diet can improve human health [1][2][3], particularly in relation to: a lower prevalence of cardiovascular disease [4][5][6][7][8][9], a possible effect on body weight and obesity regulation [10][11][12], a lower risk of type-2 diabetes mellitus [13][14][15], and to longevity improvement [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Diet is considered a milestone in diabetes primary prevention, with various dietary patterns being effective in preventing diabetes development [2][3][4]. Medical nutrition therapy (MNT) after diabetes diagnosis is of major importance.…”
Section: The Role Of Medical Nutrition Therapy In Diabetes Managementmentioning
confidence: 99%